2021
DOI: 10.1364/oe.424740
|View full text |Cite
|
Sign up to set email alerts
|

3D super-resolution microscopy based on nonlinear gradient descent structured illumination

Abstract: Three-dimensional structured illumination microscopy (3D-SIM) is an essential tool for volumetric fluorescence imaging, which improves both axial and lateral resolution by down-modulating high-frequency information of the sample into the passband of optical transfer function (OTF). And when combining with the 4Pi structure, the performance of 3D-SIM can be further improved. The reconstruction results of generally used linear 3D algorithm, however, are lack of high-fidelity and proneess to generate artifacts. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Experimental results demonstrated that introducing notch filtering can partly overcome the trade-off between increasing contrast and suppressing noise. In the same year, Zhu et al proposed an iterative algorithm called NGD-SIM based on gradient descent and a nonlinear optimizer RMSprop 149 . However, this algorithm is time-consuming.…”
Section: Development Of Sim Reconstruction Methodsmentioning
confidence: 99%
“…Experimental results demonstrated that introducing notch filtering can partly overcome the trade-off between increasing contrast and suppressing noise. In the same year, Zhu et al proposed an iterative algorithm called NGD-SIM based on gradient descent and a nonlinear optimizer RMSprop 149 . However, this algorithm is time-consuming.…”
Section: Development Of Sim Reconstruction Methodsmentioning
confidence: 99%